2011
DOI: 10.1299/jfst.6.477
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Instability and Breakup of a Viscous Compound Liquid Jet

Abstract: We analytically examine nonlinear instabilities and breakup phenomena of a viscous compound liquid jet which consists of a core and a surrounding annular phase. Applying the long wave approximation to both phases, a set of reduced nonlinear equations is derived for large deformations of the jet. Breakup phenomena are numerically examined when sinusoidal disturbances are fed at the end of the semi-infinite jet. Typical breakup profiles are shown for surface tension ratios and Reynolds numbers. In particular, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Moreover, a two-step finite difference scheme was used to study the effects of key parameters on breakup and drop formation. Other related studies are reported by Radev and Gospodinov [17], Yoshinaga and Maeda [24] and Yoshinaga and Yamamoto [25].…”
Section: Introductionsupporting
confidence: 56%
“…Moreover, a two-step finite difference scheme was used to study the effects of key parameters on breakup and drop formation. Other related studies are reported by Radev and Gospodinov [17], Yoshinaga and Maeda [24] and Yoshinaga and Yamamoto [25].…”
Section: Introductionsupporting
confidence: 56%
“…On the other hand, in the series expansion (12) for the annular phase, the expansion is considered around a mid-plane of the annular phase r = R in terms of the thickness |r − R|. Mehring and Sirignano (1999) adopted this sort of expansion ( 12) for the analysis of sinuous (antisymmetric) deformations in a planar liquid sheet and later Yoshinaga and coworkers Maeda 2008, Yoshinaga andYamamoto 2011) applied this to the annular liquid phase in a compound liquid jet. Instead of this series expansion (12), averaged quantities of velocity and pressure over the thickness could be used for the annular phase Sirignano 2000, Sano andFunakoshi 2008).…”
Section: Long Wave Approximation and Non-linear Reduced Equationsmentioning
confidence: 99%
“…Nath et al [6] conducted a temporal stability analysis of a plane liquid sheet that is subjected to different gas velocities on both sides. Yoshinaga [7] examined the breakup and encapsulation phenomena of a gas-cored compound liquid jet, which consists of an inviscid and incompressible core gas and surrounding annular liquid.…”
Section: Introductionmentioning
confidence: 99%